Association of both Water, Sanitation and Hygiene (WASH) and Infant and Young Child Feeding (IYCF) practices with childhood malnutrition in Lao PDR: a cross-sectional study of the 2017 Lao Social Indicator Survey II - Frank T Wieringa; Maiza Campos Ponce; Katja Polman; David Duncan; Somphos Vicheth Som; Prosper Dakurah; Janneke Blomberg; Sitthorot Rasphone; Marinka van der Hoeven (BMJ Open, 2023)
Objective We assessed whether Water, Sanitation and Hygiene (WASH) and Infant and Young Child Feeding (IYCF), either alone or combined, were associated with malnutrition among Lao People’s Democratic Republic (Lao PDR) children aged 6 to <24 months.Design This is a secondary analysis of the 2017 Lao Social Indicator Survey II (LSIS II), which used multistage probability proportional to size sampling. Logistic regression analyses were conducted with OR and its corresponding 95% CI.Setting The LSIS II was conducted a nationwide household-based survey covering all 18 provinces in Lao PDR.Participants We had a total of 3375 children (weighted sample 3345) and 357 households with data on drinking water.Outcome measures The outcomes of this study were stunting and wasting.Results The prevalence of stunting and wasting was 28.9% and 10.1%, respectively. Even though households with access to a basic or improved water source were high (82.5%), over 83% of drinking water was contaminated with Escherichia coli. Access to improved sanitation, basic hygiene and adequate IYCF gave a significant lower risk of becoming stunted. The combined effect of these practices on stunting was (adjusted OR (AOR)=0.54; 95% CI=0.41 to 0.73) greater than each practice alone (improved sanitation: AOR=0.75; 95% CI=0.61 to 0.93; basic hygiene: AOR=0.69; 95% CI=0.57 to 0.83; adequate IYCF: AOR=0.79; 95% CI=0.64 to 0.98). Access to improved sanitation and adequate IYCF was associated with a significant lower risk for being wasted, and again the combined effect of these practices was (AOR=0.64; 95% CI=0.44 to 0.92) greater than each practice alone (improved sanitation: AOR=0.68; 95% CI=0.49 to 0.93 and adequate IYCF: AOR=0.66; 95% CI=0.47 to 0.92).Conclusion Given the strong associations with both stunting and wasting, and the added benefits when combining WASH and IYCF, there is a need of multisectoral interventions to reduce early childhood malnutrition in Lao PDR.